Covid-19 and The Role of Islamic Economics & Finance - Aisyah As-Salafiyah; Nun Maziyyah Mahsyar (Journal of Islamic Economics Literatures, 2022)
This study aims to determine the development map of Covid-19 outbreak research that is published by journal in the theme of Islamic economics and finance. The data analyzed were more than 50 publications of indexed research publications. The entire sample journal publications have published in 2020. The export data is then processed and analyzed using the VOSviewer application program to find out the bibliometric map of the development of economic of the role of islamic economics and finance in times of Covid-19 outbreak. The results showed that the number of publications on the development of the role of Islamic economics and finance research experienced a significant increase. Network visualization showed that the map of the development of Covid-19 research was divided into 4 clusters. Cluster 1 consists of 20 topics, cluster 2 consists of 20 topics, cluster 3 consists of 11 topics, and cluster 4 consists of 12 topics. The findings of this study are that there is special attention to the development of the halal industry, especially halal food and Islamic social finance in order to mitigate the impact of the prolonged health and economic crisis.